Optimal dynamic economic dispatch including renewable energy source using artificial bee colony algorithm - Abu-Mouti, F. S.; El-Hawary, M. E. (2012 6th Annual IEEE Systems Conference, 2012)
Power utilities strive for optimal economic operation of their electric networks while considering the challenges of escalating fuel costs and increasing demand for electricity. The dynamic economic dispatch (DED) occupies a prominent place in a power system's operation and control. It aims to determine the optimal power outputs of on-line generating units in order to meet the load demand subject to satisfying various operational constraints over finite dispatch periods. Similar to most real-world complex engineering optimization problems, the nonlinear and nonconvex characteristics are more prevalent in the DED problem. Therefore, obtaining a truly optimal solution presents a challenge. In this paper, the artificial bee colony (ABC) algorithm - a recently introduced population-based technique - is utilized to solve the DED problem. Integrating a renewable-energy source and analyzing its impact is considered as well. A sample test system with a dispatch period of 24-hour is designated to validate the outcomes. The promising results prove that the ABC algorithm has a great potential to be applied in different electric power system optimization areas.